1990
DOI: 10.1038/344410a0
|View full text |Cite
|
Sign up to set email alerts
|

A sodium-potassium switch in the formation of four-stranded G4-DNA

Abstract: Single-stranded complex guanine-rich DNA sequences from chromosomal telomeres and elsewhere can associate to form stable parallel four-stranded structures termed G4-DNA by a process that is anomalously dependent on the particular alkali metal cation that is present. The anomaly, which is not found in the formation of G4-DNA by oligonucleotides containing short, single runs of three or more guanines, is caused by potassium cations excessively stabilizing fold-back intermediate structures, or pathway by-products. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

32
667
8
3

Year Published

1994
1994
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 794 publications
(710 citation statements)
references
References 27 publications
32
667
8
3
Order By: Relevance
“…At low temperatures, K+ stabilized conformations that did not lead to G-wire formation. These structures were most likely hairpin dimers (G'2-DNA), which is consistent with previous reports (Sundquist & Klug, 1989;Sen & Gilbert, 1990). Although Na+ may facilitate the formation of the same conformations as K+, it may not stabilize them as well as K+.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…At low temperatures, K+ stabilized conformations that did not lead to G-wire formation. These structures were most likely hairpin dimers (G'2-DNA), which is consistent with previous reports (Sundquist & Klug, 1989;Sen & Gilbert, 1990). Although Na+ may facilitate the formation of the same conformations as K+, it may not stabilize them as well as K+.…”
Section: Discussionsupporting
confidence: 92%
“…Many G-rich telomeric oligomers can form a family of related structures containing G-quartets (G-DNA). For example, a single repeat of the Tetrahymena telomeric G-strand sequence TGGGGT will adopt a four-stranded parallel quadruplex (Aboul-ela et al, 1992) while two repeats, (T2G4)2, can adopt either a four-stranded parallel quadruplex known as G4-DNA or an anti-parallel hairpin dimer quadruplex known as G'2-DNA (Sen & Gilbert, 1990). For the two repeat molecules, the preference of one conformation over the other is most influenced by the monovalent cation present (Na+ or K+) and DNA concentration.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Sen and Gilbert observed that the formation of the four-stranded parallel quadruplexes was anomalously dependent on the species of alkali metal cation in the solution. They proposed that the bimolecular foldback quadruplexes were "overstabilized" intermediates and expected that all of the quadruplexes that were formed by single-or double-folded strands could finally be converted to four-stranded parallel structures [30]. Miura et al, using Raman spectroscopy, detected the transition of the antiparallel bimolecular [d(G 4 G 4 )] 2 to the parallel four-stranded structure in the solution containing Na ϩ and K ϩ by changing the K ϩ /Na ϩ ratio [31].…”
mentioning
confidence: 99%